(untitled) (Indian Journal of Animal Production and Management, 2024)
The primary objective of this study was to assess the impact of Lactomix Active, a liquid mineral herbal supplement, on milk production and the overall health of dairy animals. A total of 15 crossbred animals were carefully chosen and distributed into three groups for experimentation. The first group, labeled as the Control, received no liquid supplementation. The second group, known as Treatment 1, was administered Lactomix AD3 Active, a liquid mineral supplement, daily at a rate of 100ml for a continuous 10-month period. The third group, referred to as Treatment 2, received the same liquid mineral supplement at a rate of 100ml every three days a week over the course of 10 months. The results of the study revealed that the inclusion of the liquid mineral mixture in the diets of lactating cows led to a noticeable increase in milk production (2.38±0.04 kg), milk fat content (5.9±0.13%), and milk total solids (8.5±0.31%) in comparison to the control group. Notably, the study also showed that adopting a regimen of three days per week for liquid mineral supplementation was economically advantageous, while still achieving a noteworthy improvement in the average milk yield and milk quality parameters. These findings underscore the significance of incorporating liquid mineral mixture supplementation as a means of substantially boosting the income of farmers.